Ensino de análise funcional para professores: análise dos resultados de duas linhas de pesquisa - Silvério, Juliana Helena dos Santos (2012)
In the last two decades the behavior analysis observed the emergence and growth of a line of research aimed at investigating the teaching of verbal repertoires description and functional analysis of conditions that could facilitate their teaching in applied settings. In Brazil at least two working groups study the teaching of functional analysis for teachers. The first group, UNESP Bauru, is represented by the academic work of Fonseca (2008), Sparvoli, (2008), Oliveira (2010) and Gomes (2010). The second group, the PUC SP, is represented by the works of Almeida (2009), Cerqueira (2009), Tavares (2009) and Leite (2010). The objective of this research was to analyze the data collected by these two lines of research to identify which variables were responsible for the results obtained in the teaching functional analysis and its generalization. The consistency of their methods with the principles of behavior analysis to education was investigated. The research was also aimed at identifying the difficulties mentioned by the authors propose some ways of overcoming. The results showed that the PUC SP group presented methods using experimental designs, and even used some principles of behavior analysis to education___ as the description of goals and behavioral measures, the preliminary assessment of the repertoire of the participants, the planning small steps, the constant promotion of responding to and use of a material easy to reproduce. These characteristics seem to have contributed to all the participants learn to identify the function of the behaviors presented in teaching situations. In relation to data on generalization, UNESP Bauru group achieved better results, since most of the participants managed to change their teaching practices after having gone through training. The result obtained by UNESP Bauru group may have been a function of training with multiple copies in the natural applied context. It was concluded that to meet the demands of the scientific community and service providers is necessary a careful description of methodological procedures. Repeatable and measurable variables benefit the research and the application. In addition, the following principles of behavior analysis to education, and planning of generalization, could increase the effectiveness of teaching procedures. Careful planning of the methods adopted by Almeida (2009), Cerqueira (2009), Leite (2010) and Tavares (2009), together with the applied context adopted by Fonseca (2008), Gomes (2010), Oliveira (2010) and Sparvoli ( 2008), may point to advances in behavior analytic proposals for education